Nonexistence theorem except the out-of-phase and in-phase solutions in the coupled van der Pol equation system - Nohara, B. T. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We consider a coupled van der Pol equation system. Our coupled system consists of two van der Pol equations that are connected with each other by linear terms. We assume that two distinctive solutions (out-of-phase and in-phase solutions) exist in the dynamical system of coupled equations and give answers to some problems.